American aid to Egypt and its role in political decision-making (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The article on American aid to the Arab state of Egypt, aimed to shed light on this aid and its impact on the Egyptian economy and the degree of its impact on the political decisions of the state regarding its political stances towards regional issues and crises and Egypt’s use of that aid as a tool to maintain the peace associated with the peace treaty between the state of Egypt and Israel She also referred to the aspects of this aid and its impact on the military, economic, social and cultural sectors of the Egyptian state.The problem of the research is to know the reality of American aid to Egypt in addition to the aspects of this aid and the goal of providing this aid to the Egyptian government and how it is used by the United States of America in implementing its agenda in the region and the way it is distributed and reduced in time periods and increased in other periods and knowing its impact on the Arab region and the position of Egypt is a regional issue.